PENGARUH PUASA SUNNAH DAUD TERHADAP KECERDASAN EMOSIONAL MAHASISWA MA’HAD AL-HUSAIN BIN ‘ALI - Sabirin B. Syukur; Euis Hidayat (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Emotional intelligence is needed to be able to hold someone solve problems and overcome things that are around him. Puasa Daud can have a positive impact on the psyche, mental retention, self-control, stress control, and psyhophysical therapy. Purpose of research; To know the influence of Puasa Daud on Emotonal Intelligence of Ma’had Al-Husain bin’Ali Muhammadiyah University of Gorontalo. The design of this study used Pre Experiment with One Group Pre-test and Post-test design. Sample of 15 respondents. The result of the research using Paired T-Test statistic test showed emotonal intelligence after done the fasting teratment daud got sig value. 0,000 (p <0.05). the conclusion in this research is that there is influence of Puasa Daud to Emotional Intelligence of Ma’had Al-Husain bin ‘Ali Muhammadiyah University of Gorontalo.